Prevention of Extraordinary Crimes in Kazakhstan: Legal and Procedural Aspects - GRIGORYEV, Vitaliy; AUBAKIROVA, Anna Alexandrovna (Journal of Advanced Research in Law and Economics; Vol 7 No 6 (2016): Vol 7, No 6(2016): JARLE, Volume VII, Issue 6(20), Fall 2016, 2017)
In conditions of building a modern law-governed state, the paramount importance is assigned to the problems of protection of citizens from criminal attacks and offenses, prevention of the attempts of criminalization of society, neutralization of the negative social trends, and provision of stability. Increasingly common are the cases where special and law enforcement agencies have to conduct an investigation under the conditions of emergency situations caused by riots, ethnic conflicts, terrorist attacks, and the other emergency accidents. Specific and law enforcement agencies should always pay special attention to improving the level of training and operational readiness in order to respond to new criminal manifestations. Necessary measures should be assumed to ensure their full implementation. In this context, special acuteness belongs to different issues of combating with crimes, in particular, prevention, and it is not a secret that today these systems are going through a difficult period of institutional reforms. The choice of procedural decisions to be fulfilled by the investigator, inquiry officer or body of inquiry, has always been dictated by circumstances and environment events. Many situations are often challenging, unusual and unpredictable. Therefore, police officers must be prepared for this and show mental stability, endurance and determination. The author has considered the criminal and procedural aspects of the prevention of extraordinary crimes. The article presents the author's view on the causes and conditions encouraging perpetration of a crime (riots, armed attacks on officials, etc.), and the other factors having aggravated the course of events, etc. The author offers a number of activities, implementation of which may qualitatively affect positive outcome of the conflict resolution, prevention of criminals’ activities etc.
Keywords: emergency situation, accident, criminality and crime, crime detection and investigation, preliminary investigation bodies, determinants, prevention, making representations, enforceability